The effect of using collective competition strategy in the application of professional education for students of basic sixth grade in the field of sculpture - Deb , Aossaf; Ali, Saba (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
This research aims to measure the impact of the use of collective competition strategy in the training of the sixth grade students on vocational education activities in the field of sculpture, and the number of sample basic experiment members (28) students applied to them cognitive achievement test tribal / Uday, and a final achievement test after the implementation of all activities the program, after verification of the validity and reliability, and calculated the averages and standard deviations for answers to students, were used T-test which showed a statistically significant difference between the average scores sixth-grade students in the tribal tests and the average scores in the post tests and this difference is due to the use of collective competition method, and no statistically significant differences between the mean scores of each of the targeted students study respondents appear in the post tests Bensati own program depending on the variable sex.